Apremilast is a potentially useful treatment for severe palmoplantar pustulosis with extra‐palmoplantar symptoms - Ayano Fukushima‐Nomura; Saeko Takamiyagi; Risa Kakuta; Yoshihiro Ito; Ikuko Hirai; Junichi Umemoto; Hironari Hanaoka; Yuko Kaneko; Keiji Tanese (Wiley, 2024)
Abstract Palmoplantar pustulosis (PPP) is a chronic inflammatory skin disorder affecting the palms and soles. In rare cases, severe patients develop acute extra‐palmoplantar lesions often accompanied by arthralgia. Such cases with extensive symptoms often necessitate systemic treatments with variable efficacy and potential side effects. Apremilast, known for its broad immune response modulation, presents promise as a therapeutic option for severe PPP with joint and extra‐palmoplantar lesions. This case highlights apremilast as a potential systemic treatment for such cases with minimal side effects.